Purification and kinetic characterisation of class 3 bovine corneal aldehyde dehydrogenase : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Chemistry at Massey University - Woodhead, Brendon John (Massey University, 1999)
Aldehydes can be found in a wide variety of places. For example, formaldehyde, acetaldehyde and acrolein are products of combustion and are present in smog and cigarette smoke (Schaucnstein et al., 1977). In addition, many foods, such as fruits and vegetables, are sources of aldehydes (Schauenstein et al., 1977). Aldehydes can also function as communication molecules, either between species or within a species, but the majority of aldehydes which are encountered are physiologically derived intermediates in the metabolism of other compounds (Schauenstein et al., 1977). Aldehydes can be generated from numerous endogenous and exogenous sources. Endogenous aldehydes include aldehydes arising from the metabolism of amino acids, biogenic amines, carbohydrates, vitamins, steroids (Schauenstein et al., 1977) and as a result of membrane lipid peroxidation (Esteibauer et al., 1990). Examples of some exogenous derived aldehydes include aldehydes resulting from the oxidation of primary alcohols (Williams, 1959) and from combustion (Schauensteinetal., 1977). In general aldehydes are biologically toxic due to the highly reactive nature of their electrophilic carbonyl group which can react with cellular nucleophiles, including proteins and nucleic acids. But not all aldehydes are biologically detrimental; for example, retinoic acid, the oxidation product of retinal, is involved in embryonic differentiation, and retinal itself is required for vision (Siegenthaler, et at., 1990). Some aldehydes may be chemotactic, that is they can recruit cells to sites of injury or inflammation (Dianzani, 1989).[FROM INTRODUCTION]
Keywords: Aldehyde dehydrogenase; Purification; Cornea -- Physiology